2006
DOI: 10.1002/dvdy.21054
|View full text |Cite
|
Sign up to set email alerts
|

SOST expression is restricted to the great arteries during embryonic and neonatal cardiovascular development

Abstract: Spatial-temporal regulation of bone morphogenetic protein (BMP) and Wnt activity is essential for normal cardiovascular development, and altered activity of these growth factors causes maldevelopment of the cardiac outflow tract and great arteries. In the present study, we show that SOST, a Dan family member reported to antagonize BMP and Wnt activity, is expressed within the medial vessel wall of the great arteries containing smooth muscle cells. The ascending aorta, aortic arch, brachiocephalic artery, commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…Figure 2 highlights the osteocytic expression of sclerostin in mouse, rat, monkey, and human bone. Extraosseous sclerostin expression has been described in specific regions of the developing embryonic and neonatal heart, although sclerostin expression was not detected in adult cardiac tissue (88,89). Most recently, Zhu et al (90) showed that sclerostin expression increases with calcification of vascular smooth muscle cells and expression of sclerostin in calcified aortas from the Enpp1 KO mice.…”
Section: Sclerostin and Dkk1 Expressionmentioning
confidence: 95%
“…Figure 2 highlights the osteocytic expression of sclerostin in mouse, rat, monkey, and human bone. Extraosseous sclerostin expression has been described in specific regions of the developing embryonic and neonatal heart, although sclerostin expression was not detected in adult cardiac tissue (88,89). Most recently, Zhu et al (90) showed that sclerostin expression increases with calcification of vascular smooth muscle cells and expression of sclerostin in calcified aortas from the Enpp1 KO mice.…”
Section: Sclerostin and Dkk1 Expressionmentioning
confidence: 95%
“…Sclerostin has widely been viewed as an osteocyte-specific protein, despite early studies noting SOST RNA in multiple human and mouse tissues, including cartilage, kidney, heart, and liver (1, 2, 15). More recently, using Sost promoter LacZ reporter mice, Collette, et al, further expanded this list, documenting Sost LacZ reporter expression in the epididymis and vas deferens of the testis, the pyloric sphincter, the carotid arteries, and parts of the cerebellum (16).…”
Section: Sclerostin Expression Beyond the Osteocytementioning
confidence: 99%
“…Sclerostin is a hallmark protein of osteocytes, which negatively regulates proliferation and differentiation of osteoblast, thus regulating bone formation [4][5][6][7][8]. Mechanical loading negatively regulates the expression of sclerostin and therefore, this molecule bridges mechanical loading to bone and bone metabolism [9][10][11].…”
Section: Quantitative Fluorescence Imaging In Osteocyte Biologymentioning
confidence: 99%